Economic Valuation of Pagutan Green Open Space in Mataram City as a Basic for User Fee Determination and Sustainable Management Strategy - Madyawati, Luh Putu Dyah; Diswandi, Diswandi; Maryam, St. (JURNAL ECONOMINA, 2026)
Rapid urban development is putting pressure on the availability of green open spaces and the quality of the urban environment. This study aims to analyse the economic value of Pagutan green open space from the perspective of public, formulate a fee structure and sustainable management strategy for it. The study employed a mixed-methods approach with a sequential explanatory design, combining quantitative analysis using the Contingent Valuation Method with a bidding game approach, as well as qualitative analysis through informant interviews and observation. Data were collected from 145 respondents that analysed using multiple linear regression and community participation analysis. The results indicates that the yearly total economic value of the green urban space is about Rp476.056.512 counted from visitors’ willingness to pay for its existence. Visitors’ age, income, education, visit frequency, distance from residence, and perceptions of green open spaces significantly impacting visitors’ willingness to pay. Community participation was relatively high, particularly in maintaining cleanliness and adhering to regulations, but direct involvement in maintenance activities remained moderate. Based on an analysis of ability to pay, the most realistic fee is Rp3,000/person/visit, applied selectively to the Special Sports Zone, the Environmental Education Zone/Greenhouse, and the Children’s Playground Zone. The sustainable management strategy for the Pagutan Green Open Space is divided into three categories based on the three pillars of sustainable development: the economic aspect, through the implementation of user fees as a supplementary funding source; the social aspect, through increased community participation and education; and the environmental and institutional aspects, through enhanced vegetation maintenance and strengthened area management.